Manajemen Dakwah BKMT Dalam Mencegah Pergaulan Bebas Remaja Di Kecamatan Bilah Hilir - Nurhasanah Nurhasanah; Lamuddin Lamuddin (Universitas Cokroaminoto Yogyakarta, 2025)
This qualitative study aims to determine the management of da'wah applied by the Contact Board of Majelis Ta'lim (BKMT) in an effort to prevent promiscuity among teenagers. data collecting through interviews, observation, and documentation. The results showed that BKMT's da'wah management includes four stages: planning, organizing, implementing, and supervising. Planning is arranged according to community needs with relevant materials and methods. Organizing involves various elements of society to strengthen the synergy of da'wah. Implementation is done through routine studies, seminars, and personal approaches to vulnerable youth. Supervision is carried out through program monitoring and evaluation. Support from religious leaders, communities and social media are supporting factors, while obstacles include lack of youth participation, environmental influences and limited resources. In terms of effectiveness, BKMT's proselytizing is still limited, with positive changes only occurring in a small proportion of religiously active adolescents.